Performance bond and an injunction - Ismail, Nur'ain (2007)
Claims under performance bonds have been a subject of considerable litigation in Malaysia and other jurisdictions. Performance bonds, either conditional or on-demand, are provided by contractors in favour of employers to ensure their complete performance of the contracts. When the contracrors breach the contracts, this will entitle the employers to make calls on the bonds. However, injunctions have been used by contractors to defeat the main purpose of the bonds. Injunction is an equitable remedy and is within the dsicetionary power to the judge. Judges have granted and rejected contractors applications for injunction to restrain the call on the bonds. The main issue is relating the principles used by judges in granting or rejecting an injunction. The objective of the study is to identify legal principles used by the courts in granting or rejecting an application for injunction against bondsmen from making payment or against employer from receiving the the bonds. The research methodology used in achieving this objective, was by analysis of reported and unreported court decisions of the relevant leading cases in Malaysia and other commonwealth countries. The analysis showed that: there three principles in refusing and two principles in granting an application for an injunction. The two principles for granting an injunction are fraud or unconscionably conducts regarding the making of the call or payment. The three principles for refusing are one, when there are serious issues to be tried; two, when fraud is involved; and here, when there is unconscionably conduct by contractors. However, if the court identified that there is an adequate remedy the injunction will not be granted. As conclusion, injunction to restrain the calling and obstructing the payment is not an appropriate method in solving disputes that arise between two parties. It is better to identify other alternative adequate remedies recovering the financial loss and damages.